Development of thin sound absorber by parameter optimization of multilayer compressed porous metal with rear cavity. (February 2020) - Shen, Xinmin; Bai, Panfeng; Chen, Liang; To, Sandy; Yang, Fei; Zhang, Xiaonan; Yin, Qin
Graphical abstract: Highlights: Absorption performance of porous metal was improved by compression and combination. Average sound absorption coefficient of 0.5105 was obtained with thickness of 5 mm. Consistencies of data validated effectiveness of model, optimization, and simulation. Layer-by-layer morphology characterization provided intuitive explanations. Abstract: Practicability and applicability of the sound absorber can be improved by reducing its total thickness. The thin sound absorber was developed by optimizing the multilayer compressed porous metal with the rear cavity in this research. Theoretical model of sound absorption coefficient of the multilayer compressed porous metal with the rear cavity was constructed through the transfer matrix method based on Johnson-Champoux-Allard model, and its structural parameters were optimized to obtain optimal average sound absorption coefficient in 100–6000 Hz by the cuckoo search algorithm. Finite element simulation of the sound absorbers was conducted in the virtual acoustic laboratory for preliminary verification. According to the optimal structural parameters, single compressed porous metals were prepared and assembled to the optimal multilayer compressed porous metal with the rear cavity, and their sound absorption coefficients in 100–6000 Hz were measured according to standing wave tube method. Through theoretical modeling, parameter optimization, finite element simulation, and standing wave tube measurement, an effective sound absorber with the average sound absorption coefficient of 0.5105 in the 100–6000 Hz was developed by optimal 4-layer compressed porous metal with the total thickness of 5 mm, which would promote its application in the noise reduction field.